2007
DOI: 10.1016/j.juro.2007.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Ureteral Obstruction: Outcomes After Intervention. Have Things Changed?

Abstract: The overall survival of patients with malignant ureteral obstruction remains poor. Prognostic factors for decreased overall survival and prolonged hospital stay have been identified. Although the technical success of decompression has improved the subsequent complication rate is still high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
102
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(126 citation statements)
references
References 16 publications
2
102
1
3
Order By: Relevance
“…The use of ureteral stents to bypass the obstruction is common in clinical practice, and RUS is more advantageous than PCN, particularly in view of the limited life expectancy of patients with advanced malignancies (3,4,7). However, the incidence of insertion failure is markedly higher in cases of MUO, ranging from 15.0 to 27.5% (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). This high failure rate may be associated with extrinsic compression or invasion of the ureter by tumors, which may lead to the bending and deformation of the ureter, which then increases resistance during intubation in the majority of advanced malignancies (15).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The use of ureteral stents to bypass the obstruction is common in clinical practice, and RUS is more advantageous than PCN, particularly in view of the limited life expectancy of patients with advanced malignancies (3,4,7). However, the incidence of insertion failure is markedly higher in cases of MUO, ranging from 15.0 to 27.5% (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). This high failure rate may be associated with extrinsic compression or invasion of the ureter by tumors, which may lead to the bending and deformation of the ureter, which then increases resistance during intubation in the majority of advanced malignancies (15).…”
Section: Discussionmentioning
confidence: 99%
“…Ganatra and Loughlin (11) analyzed 157 patients with MUO who underwent retrograde ureteral stent placement, and found that when invasion into the bladder was noted on cystoscopy, 55.9% (19/34; P=0.008) developed stent failure. These patients usually had large pelvic malignancies, which may directly invade the bladder or ureter and press on the renal duct (6,9). For these reasons, if a patient is found to have bladder invasion on CT or MRI, stent placement under local anesthesia is not suitable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, no consensus has been developed regarding the proper management of MEUO. 1,7 Wong et al 8 reported a minimal benefit in overall survival after decompression in patients who had metastases or a previously established diagnosis of malignant ureteral obstruction. Furthermore, another report emphasized that no factor could be identified as a predictor of an improved survival or PS after diversion.…”
Section: Discussionmentioning
confidence: 99%